Integrating artificial intelligence and optogenetics for Parkinson’s disease diagnosis and therapeutics in male mice - Bobae Hyeon; Jaehyun Shin; Jae-Hun Lee; Woori Kim; Jea Kwon; Heeyoung Lee; Dae-gun Kim; Choong Yeon Kim; Sian Choi; Jae-Woong Jeong; Kwang-Soo Kim; C. Justin Lee; et al. (Nature Communications)
Abstract Parkinson’s disease (PD), a progressive neurodegenerative disorder, presents complex motor symptoms and lacks effective disease-modifying treatments. Here we show that integrating artificial intelligence (AI) with optogenetic intervention, termed optoRET, modulating c-RET (REarranged during Transfection) signalling, enables task-independent behavioural assessments and therapeutic benefits in freely moving male AAV-hA53T mice. Utilising a 3D pose estimation technique, we developed tree-based AI models that detect PD severity cohorts earlier and with higher accuracy than conventional methods. Employing an explainable AI technique, we identified a comprehensive array of PD behavioural markers, encompassing gait and spectro-temporal features. Moreover, our AI-driven analysis highlights that optoRET effectively alleviates PD progression by improving limb coordination and locomotion and reducing chest tremor. Our study demonstrates the synergy of integrating AI and optogenetic techniques to provide an efficient diagnostic method with extensive behavioural evaluations and sets the stage for an innovative treatment strategy for PD.